Athlete Management Information System in KONI Karawang District - Bagja Nugraha (Universitas Singaperbangsa Karawang, 2020)
The Indonesian National Sports Committee or KONI is an organization that functions as a coordinating all athletes whose duty is to foster and develop the athletes become achievers in sports activities both at the regional and national levels. Koni Karawang is one of the authorized organization in coordinating every sporting activity in Karawang district and also functions as a forum for athletes in Karawang district so that it can accommodate all talented athletes so that they can be fostered further. Quite a lot of athletes in the Karawang district requires the management of data collection of athletes to be better coordinated. So, we need a system that can facilitate the management of KONI athletes in Karawang district. In this case, an Information System was created which functions to process the data of athletes in Karawang district, so that it would be assisting in the data collection of the athletes. The information system created is in the form of a website-based application with implementation using a PHP programming language and MySQL database